Trans-atlantic (mis)trust in perspective: asymmetry, abandonment and alliance cohesion - Pesu Matti; Sinkkonen Ville (Routledge, 2025)
This article clarifies the role of trust in alliances with a focus on NATO. We bridge IR scholarship on trust and alliance theory by dealing with trust as a central factor in maintaining alliance cohesion and longevity. NATO has, throughout its history, been characterised by an asymmetric trusting relationship, with Europe being more vulnerable to defection than its American counterpart. This means that a fear of abandonment, intrinsic to the structure of reciprocal commitment in all alliances, has been felt differently on the opposite sides of the Atlantic, with implications for how specific crises have led to a fluctuation in (mis)trust. Whereas the Europeans have harboured mistrust regarding the longevity of the US commitment and extended deterrence, the Americans have doubted the Europeans’ faithfulness to US leadership and willingness to share the alliance’s burdens. Simultaneously, general trust – cultivated by shared interests, institutions, interdependence and converging identities – has bound the allies together. The article then uses these insights to analyse the Trump presidency, which marked an historic spike in mistrust between the US and the Europeans. Despite the unforeseen tumult, the presidency did not result in the definitive collapse of trust in the trans-Atlantic relationship, let alone NATO.